Sage: A Community Empowered University E-Learning Application - Lim, Ronald Sheng Wei (2023)
The paradigm has shifted for the tertiary education sector as it is diving into a new era, where universities are embracing a new norm which is online learning or hybrid learning. In this process, the human interaction element of learning is lost as students are treated as an individual as opposed to a community. Now more than ever, students require a platform where they can function as a community to encourage mutual learning, discussions and sharing as an academic community together.